2020
DOI: 10.1021/acs.macromol.9b01953
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Aging and Stress Relaxation in Macromolecular Physical Gels: The Case of Strontium Alginate

Abstract: We investigate macromolecular physical gels (strontium alginates) in a wide range of aging times and length scales by combining linear stress relaxation and dynamic light scattering (DLS) experiments. Stress relaxation shows an early logarithmic decay followed by a stretched exponential behavior, leading to define two characteristic times, which increase as distinct power laws of gel age. The DLS clearly displays anomalous microscopic dynamics, with compressed exponential decay of autocorrelation functions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 56 publications
6
13
0
Order By: Relevance
“…We probe the gel response on a wider range of time scales in stress relaxation tests, where a step strain of amplitude γ0 is applied at t = 0 and σ(t), the time evolution of the stress needed to maintain such a deformation, is followed for up to 2000 s. Figure 1b shows the relaxation modulus G(t) = σ(t)/γ0 for four strain amplitudes ≤ 20%. The decay of G(t) is close to logarithmic, confirming a wide distribution of relaxation times, a behavior similar to that reported in other soft solids (alginate gels (41)(42)(43), granular media under compression (44,45), colloidal glasses in creep tests (46,47)). While the applied strain changes by a factor of 40, all G(t) curves superimpose, indicating linear viscoelastic behavior up to γ0 = 20%.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We probe the gel response on a wider range of time scales in stress relaxation tests, where a step strain of amplitude γ0 is applied at t = 0 and σ(t), the time evolution of the stress needed to maintain such a deformation, is followed for up to 2000 s. Figure 1b shows the relaxation modulus G(t) = σ(t)/γ0 for four strain amplitudes ≤ 20%. The decay of G(t) is close to logarithmic, confirming a wide distribution of relaxation times, a behavior similar to that reported in other soft solids (alginate gels (41)(42)(43), granular media under compression (44,45), colloidal glasses in creep tests (46,47)). While the applied strain changes by a factor of 40, all G(t) curves superimpose, indicating linear viscoelastic behavior up to γ0 = 20%.…”
Section: Resultssupporting
confidence: 84%
“…2c). Both the compressed exponential shape (β > 1) and the nearly linear dependence of the relaxation rate with q (a ≈ 1) have been reported for a variety of soft solids, including biological gels (14,41,(50)(51)(52)(53). They are indicative of ballistic dynamics, as opposed to the diffusive motion usually observed in polymeric and colloidal systems at thermodynamic equilibrium (49,54,55), and have been attributed to the slow relaxation of internal stresses in amorphous, out-of-equilibrium soft solids (50,56,57).…”
Section: R a F Tmentioning
confidence: 91%
“…The ability to deform is a necessary, but not sufficient condition for the uptake and release of the stress, which has been proven to be the key ingredient for the observation of an anomalous dynamics. In this context, several experimental studies, mainly on colloidal gels, have shown that the dynamics is sometimes faster than exponential, [50][51][52][53][54][55] i.e., it was observed that the intermediate scattering function F(⃗ q, t) at a typical wavevector ⃗ q can be described by a generalized exponential decay F(⃗ q, t) ∼ exp(t/τ) β (where τ is the relaxation time) with an exponent β greater than 1.0. At the microscopic level, β > 1.0 implies that particles move faster compared to standard diffusion, i.e., the motion is super-diffusive at the investigated length scale.…”
Section: Anomalous Dynamicsmentioning
confidence: 99%
“…The ability to deform is a necessary, but not sufficient condition for the uptake and release of the stress which has been proven to be the key ingredient for the observation of an anomalous dynamics. In this context, several experimental studies, mainly on colloidal gels, have shown that the dynamics is sometimes faster than exponential [50][51][52][53][54][55] , i.e. it was observed that the intermediate scattering function F ( q, t) at a typical wavevector q can be described by a generalized exponential decay F ( q, t) ∼ exp(t/τ ) β (where τ is the relaxation time) with an exponent β greater than 1.0.…”
Section: Anomalous Dynamicsmentioning
confidence: 99%